Internalisasi Nilai Pendidikan Karakter di Ponpes Haji Ya'qub PPHY Lirboyo - Ansharuddin M; Ahmad Fahroni; Arif Fajar Subekhi (CENDEKIA: Jurnal Studi Keislaman, 2021)
Pondok Pesantren Haji Ya'qub (PPHY) Lirboyo City of Kediri is one of the Islamic boarding schools that internalizes character values ​​in everyday life in pesantren. For example, religious character is embedded in the soul of the santri through congregational prayers, istighotsah, interpretation studies, and others. What also made the writer interested in making PPHY Lirboyo as a research location, this cottage is located in an urban environment. We agree that a hedonic lifestyle affects a lot of urban residents. Further research is needed on this matter. In addition, most of the students who stay in it also study public schools. This is interesting, because it has the potential to cause friction. How the respect for the kyai who is so great in the cottage environment is contrasted with the appearance of the teachers in public schools. How to limit gadgets when students are in the cottage environment, clash with conditions at school, where they are free to access gadgets, no matter how sophisticated. So questions such as whether external relationships can affect the internalization process of character values ​​in the cottage environment are interesting to be investigated further.